(untitled) (Itinera, 2025)
The aesthetic category of the grotesque has traversed the centuries, adapting to different genres and historical, philosophical, and artistic contexts, while maintaining its ability to reflect on the human condition and its contradictions through degradation, distortion, and transgression. This essay aims to analyze the grotesque as a critical lens on reality, free from judgments and rules, with particular attention to the cinema of Yorgos Lanthimos, in which it becomes a privileged tool for deconstructing social conventions and power mechanisms. In works such as Dogtooth and The Lobster, dynamics of power, madness, hypocrisy, loneliness, and alienation emerge, revealing a society built upon human fragility; whereas in The Favourite and Poor Things! the grotesque manifests itself through caricatural and paradoxical figures that challenge the very notion of normality. The goal is to show how, in Lanthimos’s film language and, more broadly, in any form of artistic expression, the grotesque assumes a critical and cognitive function, offering a perspective capable of illuminating contemporary reality in its ambiguous nature, constantly oscillating between the comic and the tragic, the absurd and the real.